Colony Breeding Structure of Reticulitermes (Isoptera: Rhinotermitidae) in Northwest Arkansas - Janowiecki, Mark Allan; Tripodi, Amber D; Vargo, Edward L; Szalanski, Allen L (Sociobiology, 2019)
Termites, as social insects, have a complicated life cycle in which the colony breeding structure, that is the number of and origin of reproductives in a colony, can vary in relation to age and environmental factors. In this study, we used genetic methods to characterize the breeding structure of three species of Reticulitermes from three sites in northwest Arkansas and compared two habitats: undeveloped, forested sites and developed, agricultural sites. We found 57.1% of R. flavipes (Kollar) in northwest Arkansas (n = 28) were simple families, 39.3% were extended families and 3.6% were mixed families. Similarly, for R. hageni Banks (n = 23), we found 58.3% simple families, 33.3% extended families, and 8.3% mixed families. All of the R. virginicus (Banks) samples (n = 5) were simple families. For R. flavipes and R. hageni, the percentage of extended families is intermediate to southeastern and northern USA populations, corresponding to the intermediate seasonality and climate in Arkansas. The level of inbreeding in Arkansas, estimated via FIT, was relatively high and similar to northern populations of Reticulitermes. There were significantly more extended family colonies at the developed site compared to the two undeveloped sites which contained more simple family colonies. This difference may occur as a strategy to cope with sparse resources in urban environments or as a consequence of different abiotic factors.